Whole exome sequencing identifies genomic alterations in proximal and distal colorectal cancer - Ryia-Illani Mohd Yunos; Nurul-Syakima Ab Mutalib; Sheau Sean Khor; Sazuita Saidin; Mohd Ridhwan Abd Razak; Norshahidah Mahamad Nadzir; Zuraini Abd. Razak; Isa Mohamed Rose; Ismail Sagap; Luqman Mazlan; Nadiah Abu; Rahman Jamal (Progress in Microbes and Molecular Biology)
Majority of colorectal cancer (CRC) patients are presented with advanced disease at diagnosis, particularly in cases of proximal CRCs. Little is known about the relationship between the genetic landscape and the anatomical location of the tumour; as well as the prognostication in CRC patients. The objectives of this study were to determine the somatic single nucleotide variants (SNV) and the cellular pathways between the proximal and distal CRCs. Whole exome sequencing was performed on the Ion Proton platform on 10 pairs of normal and CRC samples. The sequencing results were analysed using the Torrent Suite Software and the variants were annotated using ANNOVAR; followed by validation with Sanger sequencing. APC is the most frequently altered gene in both proximal and distal CRCs. KRAS and ATM genes were particularly altered in the proximal CRCs with a frequency of 60% and 40%, respectively. On the other hand, TP53 mutations did not show any CRC anatomical predominance. There were five recurrent novel variants in proximal CRCs and no recurrent variants identified in distal CRC. Wnt signalling pathway was the most frequently altered pathway in both proximal and distal CRCs whereas TGF-β and PI3K signalling pathways were predominantly altered in the proximal CRCs. We found that proximal CRCs presented with more variants and different altered pathways as compared to distal CRCs. However, further study in a larger series of samples coupled with functional studies will be required to confirm the identified variants and determine their roles in the pathogenesis of proximal and distal CRCs.